Fast and Early Mandibular Osteodistraction: The Long-Term Follow-Up of Mandibular Distraction Osteogenesis on Teeth Position. Issue 8 (November 2015) - Cascone, Piero; Basile, Emanuela; Saccucci, Matteo; Di Carlo, Gabriele; Angeletti, Diletta; Ramieri, Valerio; Polimeni, Antonella
Abstract : Abstract: Pierre Robin Sequence is a congenital pathology defined by the triad micrognathia, glossoptosis and often a U-shaped cleft of soft palate. Newborns affected by airways obstruction may necessitate more invasive options: tongue-lip adhesion, tracheostomy and mandibular distraction osteogenesis. The authors analyzed the effect of fast and early mandibular osteodistraction on deciduous dental development in patients affected by Pierre Robin Sequence. Analysis of the patients treated for severe form was performed by a team composed by maxillofacial surgeons and dentists. Five patients were included for the analysis: before and long term clinical and radiological assessments were considered. All patients underwent fast and early mandibular osteodistraction; two years follow up computed tomography and panorex reconstructions showed bone consolidation, 33 of 35 teeth analyzed before ostedistraction are present after distraction protocol; no positional changes were detected at the follow up analysis either deciduous teeth and molar permanent buds. No deformities regarding molar buds were detected. In conclusion external mandibular distractor devices have been associated with dental injuries and facial scaring. Even though, the dental complications identified can not be unambiguously connected to the external distractor devices.